Effect of Active MgO on Compensated Drying Shrinkage and Mechanical Properties of Alkali-Activated Fly Ash–Slag Materials - Hongqiang Ma; Shiru Li; Zelong Lei; Jialong Wu; Xinhua Yuan; Xiaoyan Niu (Buildings)
The influences of MgO activity and its content on the mechanical properties, drying shrinkage compensation, pore structure, and microstructure of alkali-activated fly ash–slag materials were investigated. Active MgO effectively compensated for the alkali-activated materials’ (AAMs’) drying shrinkage. The drying shrinkage increased rapidly with the increase in curing age and stabilized after 28 d. Within a certain range, the material’s drying shrinkage was inversely proportional to the content of active MgO. The higher the activity of MgO, the lower the drying shrinkage of the AAMs under the same MgO content. The drying shrinkage values of the test groups with 9% R-MgO, M-MgO, and S-MgO at 90 d were 2444 με, 2306 με, and 2156 με, respectively. In the early stage of hydration, the addition of S-MgO reduced the compressive strength. As the content of M-MgO increased, the compressive strength first increased and then decreased, reaching a maximum of 72.28 MPa at an M-MgO content of 9%. The experimental group with 9% M-MgO exhibited higher compressive and flexural strengths than those with 9% S-MgO and R-MgO, demonstrating better mechanical properties. The results of this study provide an important theoretical basis and data support for the optimal application of MgO in AAMs. MgO expansion agents have great application potential in low-carbon buildings and durable materials. Further research on their adaptability in complex environments will promote their development for engineering and provide innovative support for green buildings.